AB0756 Cutaneous leukocytoclastic angiitis: Study of 162 patients. (23rd January 2014) - Rueda-Gotor, J.; Loricera, J.; Calvo-Río, V.; Ortiz-Sanjuán, F.; González-Lόpez, M.; Fernández-Llaca, H.; González-Vela, M.; González-Gay, M.; Blanco, R.
Abstract : Background: Cutaneous leukocytoclastic angiitis (CLA) was defined by the International Consensus Conference for the nomenclature of the Vasculitis (Jennette et al, Chapel Hill, 1994) as an isolated cutaneous vasculitis without systemic vasculitis or glomerulonephritis. Objectives: Our aim was to evaluate the clinical features, treatment and outcome of patients with CLA. Methods: From a large series of patients with cutaneous vasculitis; those diagnosed with cutaneous vasculitis in the setting of connective tissue diseases, malignancies, infections, primary systemic necrotizing vasculitis and other entities such as Henoch-Schoenlein purpura and Essential Mixed Cryoglobulinemia were excluded from this analysis. Patients with systemic involvement including gastro-intestinal or renal involvement (glomerulonephritis) were also excluded. The remaining patients were classified as having CLA. Results: According to the above mentioned methodology, 162 patients (82 men and 80 women), with a mean age of 45.77±24.34 years (range, 1 to 95 years) were diagnosed as having CLA. Precipitating events were found in 104 (64.2%) patients. A history of drug intake before the onset of the vasculitis was found in 80 (49.4%) patients and a previous history of upper respiratory tract infection in 53 (32.8%) patients. The most frequent drugs taken shortly before the onset of the cutaneous vasculitis were β-lactamids (32 cases), NSAIDS (16 cases) and diuretics (4 cases). The most frequent clinical manifestations were cutaneous (100%), joint manifestations (41.3%) and fever (16%). The main laboratory data were elevated ESR (49.4%), leukocytosis (16.9%), anemia (9.3%), positive Rheumatoid Factor (14.8%), positive ANA (14.8%), hypocomplementemia (C3 and/or C4) (25.4%), cryoglobulins (13.58%) and positive ANCA (1.23%). The treatment included NSAIDS (21.6%), Corticosteroids (17.3%), Colchicine (2.5%) and Azathioprine (1.2%). After a mean follow-up of 15.05±33.3 months (median, 3 months), relapses were observed in 22.2% of patients. Finally, a complete clinical recovery was observed in all cases. Conclusions: CLA is usually a benign syndrome, often secondary to drugs or infections, or both. Its main clinical features are skin and joint manifestations. Its prognosis is very good. References: Jennette JC, Falk RJ, Andrassy K, Bacon PA, Churg J, Gross WL, Hagen EC, Hoffman GS, Hunder GG, Kallenberg CG, et al. Nomenclature of systemic vasculitides. Proposal of an international consensus conference. Arthritis Rheum.1994;37:187-92. Disclosure of Interest: None Declared